The empirics of technology, employment and occupations: lessons learned and challenges ahead - Fabio Montobbio; Jacopo Staccioli; Maria Enrica Virgillito; Marco Vivarelli (Global Labor Organization (GLO), 2022)
What have we learned, from the most recent years of debate and analysis, of the future of work being threatened by technology? This paper presents a critical review of the empirical literature and outlines both lessons learned and challenges ahead. Far from being fully exhaustive, the review intends to highlight common findings and main differences across economic studies. According to our reading of the literature, a few challenges-and also the common factors affecting heterogeneous outcomes across studies-still stand, including (i) the variable used as a proxy for technology, (ii) the level of aggregation of the analyses, (iii) the deep heterogeneity of different types of technologies and their adopted mix, (iv) the structural differences across adopters, and (v) the actual combination of the organisational practices in place at the establishment level in affecting net job creation/destruction and work reorganisation.
Keywords: O33; 330; Technology; Employment; Skills; Occupations; Tasks; Future of Work